PENGARUH ORIENTASI KONSUMEN, INOVASI PRODUK DAN KEUNGGULAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN - Saguna, Pande Gede Milantara; Respati, Ni Nyoman Rsi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.02.TAHUN.2024DO - 10.24843/EEB.2024.v13.i02.p17, 2024)
This study aims to determine the effect of market orientation, product innovation, and superiority of brand image on purchasing decisions at the Promise Jiwa Coffee Shop in Denpasar City. This study uses a qualitative method with a sample of 130 consumers of Jiwa in Denpasar City. Samples were taken by purposive sampling technique. The data analysis technique in this study used statistical analysis consisting of the F-test, t-test, multiple linear regression, and determination. The results showed that partially market orientation had a positive and significant effect on purchasing decisions at the Promise Jiwa Coffee Shop in Denpasar City, product innovation had a positive and significant impact on purchasing decisions at the Promise Jiwa Coffee Shop in Denpasar City, and the superiority of brand image had a positive and significant effect. on purchasing decisions at the Promise Jiwa Coffee Shop in Denpasar City. Meanwhile, simultaneously market orientation, product innovation, and superiority of brand image have a positive and significant impact on purchasing decisions at the Promise Jiwa Coffee Shop in Denpasar City.